The Influence of Brand Awareness Advertising on Instagram on Interest in Purchasing Azarine Products: (Case Study of Azarine Consumers in Bandung City) - Herliani, Alicha; Hegiarto, Aldy Santo (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
The purpose of this study is to determine the impact of brand awareness of Instagram ads on the tendency to buy Azarine products. This research is based on the phenomenon of low interest in buying Azarine products which may be caused by a lack of interest. The participants in this study were Azarine customers in Bandung City. The research was conducted with a sample size of 100 respondents and purposive sampling technique. Testing uses simple linear regression to validate the hypothesis. For the purpose of processing research data, IBM SPSS version 26 software for Windows is required. Brand Awareness is the independent variable, and consumer purchase intention is the dependent variable. In Bandung City, the Brand Awareness variable significantly and positively affects consumers' desire to buy Azarine products, with a significance level (Sign.) of 0.000 < 0.05. As a result, customers will be more likely to buy Azarine goods and will be more aware of the brand.